Body Image Disturbances Have Impact on the Sexual Problems in Chinese Systemic Lupus Erythematosus Patients - Biyu Shen; Yan He; Haoyang Chen; Chunmei Zhao; Li Zhu; Yingying Gao; Yunli Ren; Xueqing Wang; Jingwei Liu (Journal of Immunology Research)
SLE might affect all aspects of life including sexual functioning; previous study found that body image disturbance (BID) was the most powerful predictors of impaired partner relationships and sexual function. The current study investigated the relationship among disease parameters, quality of life, the psychological status, BID, and sexual problems in Chinese patients with SLE. A self-report survey design was administered to 168 SLE patients and 210 healthy individuals. Our results showed that 86 (55.1%) SLE patients reported impaired relationships with a sexual partner or partners, and 100 (64.1%) patients reported impaired sexual function which were significantly higher than the control group (31.6%, 35.7%, rep.). Age, marital status, depression, and BIDQ were the most powerful predictors of impaired partner relationships, while BIDQ3 and education, disease activity, and depression were the most significant causes of impaired sexual function. The study for first time reported Chinese SLE patients had sexual problems and BID was associated with sexual problems. So, early detection and interventions might not only rehabilitate the patients and their loved ones, but also improve overall health outcomes and reduce the direct and indirect costs of their medical care.